Perancangan Sistem Informasi Inventori Barang Berbasis Web Menggunakan Metode Waterfall - Anjas Kosasih; Ardila Putri Nur K.D.; Muhamad Reza Ghifari (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
Inventory recording for goods or products involves recording both outgoing and incoming transactions. Outgoing recording refers to the transactions or orders for goods as per the supplier or customer requests, which are then recorded by the warehouse personnel. On the other hand, incoming recording involves adding stock of goods or raw materials, which is recorded by the warehouse personnel. In the case of the inventory being researched by the author, the process of recording outgoing and incoming goods is still manual, utilizing Microsoft Office Excel. This is because the application does not have the capability to store data and information centrally in a database. To address this issue, the author has transitioned from the previous manual process to a computerized system. This allows for more accurate and precise recording of outgoing and incoming goods, with data displayed centrally, resulting in increased effectiveness and efficiency.